Estudo Comparativo entre os Constituintes Voláteis Liberados por Machos Ceratitis Capitata e Anastrepha obliqua (Diptera: Tephritidae) e seus Frutos Hospedeiros Preferencial Averrhoa carambola L. e Secundário, Carica papaya L. - Silva, Carlos Eduardo da (2005)
Males of fruit flies (Diptera: Tephritidae) release a complex blend of chemical constituents to attract co-especific males and females (aggregation pheromone). Males fruit fly from the genus Bactrocera use chemicals acquired from their host by feeding as part of their aggregation pheromone. Considering this information, studies were carried out aiming to find out if the chemical constituentes relesead by preferencial, Averrhoa carambola L. (Oxalidaceae) and alternative, Carica papaya L. (Caricaceae) fruit hosts, whose fruit fly larvae fed on these fruits, exert any influence in the chemical composition of the odours released by calling males of Ceratitis capitata and Anastrepha obliqua. In addition, a correlation between the time when the majority of C. capitata males displayed the calling behaviour and the amount of chemical constituents released by them was also studied. The volatile constituents released by calling males of the two fruit fly species and their mature host fruits were extracted by means of headspace technique using Tenax® and activated charcoal as adsorvents and desorptions were carried out by use of HPLC grade n-hexane. The results demonstrated that the chemicals found exclusively in papaya fruits were also present in extracts of C. capitata and A. obliqua calling males, including linalol, which was not found amongst the volatiles released by starfruits and also in extracts of fruit flies whose larvae fed on this fruit, showing that the volatile compounds ingested by these insects at the larval stage may be used by adults as part of their sex pheromone bouquet. The time period which ranges from 6h00 to 9h00, which corresponds to the period when most males of C. capitata display courtship and calling behaviours was the time when the obtained extracts presented the most complex mixture of compounds and thus, it was considered the best time of day for collection of volatiles released by males of this species.